2018
DOI: 10.1302/0301-620x.100b4.bjj-2017-0917.r1
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive spinal decompression for degenerative lumbar spondylolisthesis and stenosis maintains stability and may avoid the need for fusion

Abstract: Microendoscopic laminotomy is an effective form of surgical treatment for patients with DS and stenosis. Preservation of the stabilizing structures using this technique prevents postoperative instability. Cite this article: Bone Joint J 2018;100-B:499-506.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 24 publications
1
61
0
Order By: Relevance
“…However, spondylolisthesis has been indicated to rarely progress in adults (22). Recent studies have demonstrated that the additional fusion may not yield obvious clinical improvements over decompression alone, particularly when minimally invasive decompression is used (1,9). The extent of resection of the articular joint or ligamentous elements exhibits a strong influence on the degree of spinal instability (23).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, spondylolisthesis has been indicated to rarely progress in adults (22). Recent studies have demonstrated that the additional fusion may not yield obvious clinical improvements over decompression alone, particularly when minimally invasive decompression is used (1,9). The extent of resection of the articular joint or ligamentous elements exhibits a strong influence on the degree of spinal instability (23).…”
Section: Discussionmentioning
confidence: 99%
“…Minimally invasive decompression, which involves a small incision, causes significantly less tissue disruption than open surgery and provides greater patient satisfaction, and is increasingly and more frequently used for DLS (8). Certain studies have indicated that microendoscopic laminotomy is also an effective procedure for the treatment of patients with DLS (8,9). Minimally invasive decompression may prevent post-operative instability and lead to the preservation of stabilizing structures, avoiding the requirement for fusion.…”
Section: Efficacy Of Percutaneous Transforaminal Endoscopic Decompresmentioning
confidence: 99%
See 1 more Smart Citation
“…While lumbar spinal stenosis can be congenital [2], the most common cause of lumbar spinal stenosis is degenerative spondylosis [3], which commonly affects the elderly population. In fact, lumbar spinal stenosis is a leading cause of disability in the elderly [4][5][6][7][8][9][10][11][12] with reported rates as high as 11.2% in the 70-80-year-old population. Moreover, lumbar spinal stenosis poses a significant socioeconomic burden to patients and was associated with $1.65 billion in Medicare costs in 2009 [13].…”
Section: Introductionmentioning
confidence: 99%
“…Surgical approaches generally include anterior and posterior approaches. Different surgical methods and approaches should be selected according to individual conditions [6]. However, traditional surgery may lead to injury to the adjacent vital organs, muscle detachment and excessive resection of the facet joints.…”
Section: Introductionmentioning
confidence: 99%